Bunch cultural practices to optimize yield and fruit characters in banana (musa AAA Robusta) - Pijush Kanti Biswas (Department of Pomology and Floriculture, College of Agriculture, 2006)
The present investigation was carried out to standardize bunch cultural practices for improving bunch size and finger qualities of banana variety Robusta. The experiment also aimed at obtaining maximum number of fingers from a bunch having export standards. The experiment was conducted in the Department of Pomology and Floriculture, College of Agriculture, Vellayani, Thiruvananthapuram, during 2005-2006. Fourteen different treatments (including control) were imposed in this experiment. The treatment comprised of various combinations of growth regulators (GA 50 ppm and NAA 25 ppm) and organic sprays (vermiwash, cow’s urine, coconut water) as well as cultural practices (dehanding one or two apical hands, bunch cover using polythene tube) along with a control (without any treatments). The growth regulators and organic sprays were applied one month after emergence of the bunch. The experiment was laid out in randomized block design (RBD). There were two replications. The salient findings of the investigation are mentioned below. The bunch weight, bunch length, weight of hands, weight of fingers, pulp weight and sugar content increased while bunch maturity period decreased by the application of the treatment T10 i.e., removing one apical hand and spraying 50 ppm GA, one month after bunch emergence. The results also showed that bunch shape index, finger girth, TSS content and shelf life increased whereas acidity decreased when the treatment T¬11 (removal of two apical hands and spraying of 50 ppm GA one month after bunch emergence) was imposed. The finger length and number of fingers falling in the acceptable range were also improved by application of GA 50 ppm clubbed with one or two apical hands. At last, it can be concluded that trimming of one or two apical hands and application of GA at the rate of 50 ppm one month after bunch emergence, improved bunch characters, finger characters and quality of fruits.